2011
DOI: 10.4212/cjhp.v64i5.1068
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Glucommander Method of Adjusting Insulin Infusions in Critically Ill Patients

Abstract: Background: Intensive glycemic control has been associated with reduced morbidity and mortality in critically ill patients. Web-based, patientspecific insulin nomograms may facilitate improved glucose control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…These results placed VMC in the top 10% of all U.S. hospitals for HAC-8 compliance (38). Research has documented the improved performance of eGMS systems compared with paper algorithms (23)(24)(25)(27)(28)(29)31,39). However, it has been difficult to determine what factors are responsible for this superiority.…”
mentioning
confidence: 99%
“…These results placed VMC in the top 10% of all U.S. hospitals for HAC-8 compliance (38). Research has documented the improved performance of eGMS systems compared with paper algorithms (23)(24)(25)(27)(28)(29)31,39). However, it has been difficult to determine what factors are responsible for this superiority.…”
mentioning
confidence: 99%
“…Yet the goal of achieving this control remains elusive due to the limitations of our current open loop methods [4] that still require manual testing of glucose values, entry of the measured value into local or web based glucose control software, and manual adjustment of the intravenous pumps infusing insulin into the ICU patient. In order to improve overall glucose control, ICU care givers will need to be empowered with a closed loop glucose control system.…”
Section: Is Closed Loop Glucose Control For Icumentioning
confidence: 99%
“…Computerized insulin infusion protocols such as Glucommander (Glytec, Greenville, SC) have been demonstrated to improve glycemic control, decrease the risk of calculation errors, and can provide reminders for BG checks. [15][16][17][18][19][20][21][22][23] A recent study demonstrated a 98.2% adherence rate to the insulin dose prescribed when using the Space GlucoseControl system (B. Braun, Melsungen, Germany). 23 However, errors can still occur in sampling interval, data entry, and pump programming.…”
Section: Nurse-managed Insulin Infusion Protocolmentioning
confidence: 99%